Company Income Tax and Business Investment. (21st May 2022) - Freebairn, John
Abstract: There are many financial paths that link different savers who provide funds to different business investors. Path options considered include combinations of corporate and unincorporated businesses, resident and non‐resident savers, debt and equity, and distributed and retained earnings. These different financial paths have different mixes of attributes valuable to savers and investors. As a result, the options are imperfect substitutes. Australian capital income taxation varies across the different financial path options. As a result, effective tax rates and the effects of reforms to company income tax vary across the funding options. Together, the imperfect substitute and different tax treatments reduce the impact of proposed changes in company income taxation on incentives to, and rewards from, business investment.